Public Theatre and the Enslaved People of Colonial Saint-Domingue - Prest, Julia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"[This] is an exciting and impressive project that presents the first study of public theatre and slavery in the French colony of Saint-Domingue. Prof. Prest brings to bear a remarkable corpus of sources, from notarial records and eyewitness accounts to newspaper adverts, published treatises, and the texts of plays, to advance a series of significant, groundbreaking findings." -Christy Pichichero, George Mason University, Fairfax, USA "'Un-silencing' the enslaved Haitians who built the theaters, changed the scenery, and played the accompaniments, Julia Prest discovers new worlds backstage in the theaters of eighteenth-century Saint-Domingue-an exemplary study in the method and imagination required of voicing muted histories." -Joseph Roach, Yale University, Connecticut, USA The French colony of Saint-Domingue (now Haiti) was home to one of the richest public theatre traditions of the colonial-era Caribbean. This book examines the relationship between public theatre and the enslaved people of Saint-Domingue-something that is generally given short shrift owing to a perceived lack of documentation. Here, a range of materials and methodologies are used to explore pressing questions including the 'mitigated spectatorship' of the enslaved, portrayals of enslaved people in French and Creole repertoire, the contributions of enslaved people to theatre-making, and shifting attitudes during the revolutionary era. The book demonstrates that slavery was no mere backdrop to this portion of theatre history but an integral part of its story. It also helps recover the hidden experiences of some of the enslaved individuals who became entangled in that story. Julia Prest is Professor of French and Caribbean Studies at the University of St Andrews, Scotland, UK. She has published widely on early-modern French and Caribbean theatre, opera and dance, and is the creator of the trilingual (English-French-Kreyòl) Theatre in Saint-Domingue, 1764-1791 performance database: 'theatreinsaintdomingue.org'. She has collaborated with theatre-makers to create new works that bring colonial-era theatre to today's audiences, and her edited collection, Colonial-Era Caribbean Theatre: Issues in Research, Writing and Methodology is forthcoming in 2023.
1 Introduction -- 2 Mitigated Spectators: Enslaved People in the Playhouse -- 3 Unsustainable Tensions: 'Slave Ownership' among Theatre-Makers -- 4 Mitigated Portrayals: Enslaved Figures in Creole Repertoire -- 5 Concealed Contributors: Enslaved Participation in Theatre-Making -- 6 New Citizens: Shifting Roles in Revolutionary-Era Theatre -- 7 Conclusion.
Keywords: Theater -- History; Theater; Imperialism; America -- History; Theatre History; Global and International Theatre and Performance; Imperialism and Colonialism; History of the Americas